Relationship Between Organophosphate Pesticides Exposure and Hemoglobin Levels of Pesticide Spraying Farmers - Nasruddin Syam; Syamsir, Musfirah Ramadhani; Abd. Gafur (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2023)
The use of pesticides is very important in preventing and controlling pests on plants. However, the continuous use of pesticides can cause health problems, one of which is causing abnormalities in blood profile.. Purpose: The purpose of this study was to determine the relationship between organophosphate pesticide exposure and hemoglobin levels of pesticide spraying farmers in Mamappang Hamlet, Barugae Village, Mallawa Sub-District, Maros Regency in 2023. The research conducted was analytical observational research using a cross sectional approach. The population in this study were farmers spraying organophosphate pesticides in Mamappang Hamlet, totaling 70 people and the research sample was 60 farmers in Mamappang Hamlet. Data analysis was performed using the chi square correlation test. The results showed that there was no relationship between the duration of spraying (p = 1.000) and the use of PPE (p = 0.132) with hemoglobin levels and there was a relationship between the frequency of spraying (p = 0.031) with hemoglobin levels of pesticide spraying farmers in Mamappang Hamlet. There is an association between spraying duration and PPE use with hemoglobin levels and an association between spraying frequency and hemoglobin levels. To prevent the negative effects of pesticides on the body, farmers are expected to apply pesticides according to instructions and routinely conduct health checks.